Description of athlete physical conditions of sports at volleyball and basketball ball games at learning education and training center (pplp) dispora riau province in 2018 - Zainur; Aref Vai; Triana Risca Enita (Pendidikan Kepelatihan Olahraga FKIP Universitas Riau, 2019)
The purpose of this study was to find out the description of the physical condition of volleyball athletes and basketball of students education and training center (PPLP) in the Province of Riau Province in 2018, and to find out the differences in physical conditions of volleyball athletes, basketball students education and training centers (PPLP ) Riau Province Dispora in 2018. The type of this research is Quantitative Descriptive, where this study will clearly illustrate the PPLP test data from the Riau Province Physical Conditions team. Based on the results and discussion, it can be concluded that the results of the physical condition data of PPLP Volleyball athletes and PPLP basketball in Riau Province in 2018 are as follows: Physical condition of PPLP Volleyball Women's athletes in Riau Province in 2018 are in good category with a percentage of 12.5%, medium category which is 3 people with a percentage of 37.5%, the less category which is 3 people with a percentage of 37.5, and the category is very less which is 1 person with a percentage of 12.5%. While the physical condition of PPLP Women's Basketball athletes in Riau Province in 2018 is in the good category which is 1 person with a percentage of 20%, there are medium categories of 2 people with a percentage of 40%, the less category which is 2 people with a percentage of 40%, while there is no very less category. Thus, the condition of PPLP Women's Basketball Ball athletes is better than the condition of PPLP Women's Volleyball athletes